A new species of Hoplognathoca Suárez, 1962 from Central America and description of male of Hoplognathoca costarricensis Suárez, 1962 (Hymenoptera: Mutillidae) - Roberto, Cambra T. A.; Diomedes, Quintero A; Brothers, Denis J. (Zootaxa, 2014)
Hoplognathoca jinotega Cambra, Quintero & Brothers, sp. nov., female, from Nicaragua and Guatemala and the male of H. costarricensis Suárez, 1962 are described and illustrated. The genus Hoplognathoca is reported for the first time from Nicaragua.